Controlled fabrication of uniform Cu(OH)2 nanobelts via wet chemistry method. Issue 169 (12th February 2016) - Gao, Qiuyue; Liu, Yi; Zhi, Mingjia; Hong, Zhanglian
ABSTRACT: In this study, one-dimensional (1D) uniform Cu(OH)2 nanobelts have been synthesized by a facile wet chemistry method. The effect of different synthesis parameters on the morphologies of the target products was systematically studied. The uniform nanobelts can be easily controlled by different reaction time and temperature, while the quantity of ammonia adding in the solution has no obvious effect on the morphologies of Cu(OH)2 nanobelts. The optimum preparation condition of Cu(OH)2 nanobelts was that 0.42 g Cu(NO3 )2 3H2 O and 19 mL NH3 H2 O solution was added into 100 mL of distilled water and heated at 60°C for 2 hours, and the morphologies and composition of the prepared samples were characterized by SEM, TEM and XRD, respectively.